La audiencia como garantía de los principios de inmediación y tutela judicial efectiva en los procesos de apelación en justicia constitucional - Cruz Tobar, Marcelo Alexander (2023)
ABSTRACT: The main objective of this research entitle "La audiencia como garantía de los principios de inmedición y tutela judicial efectiva en los procesos de apelación en justicia constitucional", with a specific focus on the Republic of Ecuador. This research found a contradiction between the Constitution of the Republic of Ecuador and the Organic Law of Jurisdictional Guarantees and Constitutional Control related to binding jurisprudence and its application in appeal, proceedings. A dilemma was detected on the one hand, the Constitution of the country holds that jurisdictional guarantees must be oral during all stages of the legal process. On the other hand, the Organic Law and jurisprudence affirm that deciding by writs does not imply any violation of the principle of immediacy and the right to effective judicial protection. This poses a challenge since these decisions are intrinsically linked to the right of defense and, therefore, to the right to be heard. The objective was whether the lack of a hearing in appeal proceedings, when optional, infringes the principles of immediacy and effective judicial protection. To achieve this objective, a qualitative methodology was used with a non-experimental, cross-sectional, documentary, and bibliographic design, incorporating an inductive and descriptive approach. During the constitutionality check, it was found that allowing the presence of the procedural parties to be optional produces a violation of the rights. This violation directly affects the right to contradiction, immediacy, and orality. To examine this problem in depth, the study explored international entreaties and conventions, as well as Ecuador's domestic legislation and legal doctrine. The result was an unpublished word on the subject that concluded by confirming the existence of a violation of the right to defense, immediacy, and effective judicial protection as a right and principle, with a particular focus on the right to be heard. Consequently, this research highlights the need to review how hearings are handled in appeal proceedings, with the ultimate aim of guaranteeing respect for immediacy, orality, and the right to defense in constitutional justice.